A study on the factor that affecting job performance among employees at Tradewinds (M) Berhad / Siti Amira Liyana Abdul Jalil - Abdul Jalil, Siti Amira Liyana (2015)
“A study on the factors that affect job performance among employees at Tradewinds (M) Berhad, Kuala Lumpur”. Employee is one of the an important asset in the organization. Organization performance depends on employees in organization and job performance that employee can achieve. This paper aims to study factors that determine job performance among employees in organizations at Tradewinds (M) Berhad, Kuala Lumpur. The independents variables that involved in this study which are reward, personal problem, work environment and last is motivation. The dependent variable is job performance. For this project paper, this research focused on the employees been worked at Tradewinds (M) Berhad, Kuala Lumpur. 70 questionnaires were distributed to employees. The questionnaires were used to obtain and collected the data from the respondent. Cluster area sampling has been used in this study as a sampling technique. The researcher used SPSS program version 20.0 where the researcher has used reliability analysis, frequency analysis, correlation analysis and also regression analysis. In the end of this paper, the researcher has provided several recommendations regarding the factors that affect job performance among employees in organizations at Tradewinds (M) Berhad, Kuala Lumpur.